Neoadjuvant radiotherapy in stage I cancer of the lower rectum - Reis Neto,José Alfredo dos (2016)
ABSTRACT INTRODUCTION: The mortality rate in low rectal cancer is related to pelvic and distant recurrence. For stage I tumors, local excision has being used increasingly, but recent studies show the need for caution with the use of this technique, as they do not consider the possibility of a positive node in stage I rectal tumors. Therefore, preoperative radiotherapy should be considered for early tumors, as an attempt to prevent recurrence. OBJECTIVE: Show the effectiveness of neoadjuvant radiotherapy in stage I cancer of the lower rectum of a cohort population. MATERIAL AND METHOD: A cohort study in a prospective database was made with a total of 538 patients, of which were considered 75 patients with stage I lower rectal cancer. Preoperative radiotherapy was performed and patients were followed up for a minimum period of five years. RESULTS: Stage I/TI group had 27 patients. All of them presented complete response to the treatment and did not need to be operated. During the follow up time of five years, this group showed no recurrence rate. The stage I/TII group had 48 patients. During the follow up, 8 patients had to be operated due to suspicious lesion or scar. They were submitted to full total local excision. After evaluating the pathological specimen, none of them proved to be adenocarcinoma. CONCLUSION: Preoperative radiation, not only reduced the local recurrence and mortality rate in lower rectal cancer, but also reduced the need for surgery in patients with stage I cancer.